Perancangan Sistem Presensi Siswa Dengan RFID Berbasis IoT Menggunakan NodeMCU ESP8266 - Suliswaningsih Suliswaningsih; Nugie Dwitama; Anugerah Bagus Wijaya (P3M Politeknik Negeri Cilacap, 2024)
Dewantara Sumbang Vocational School has 4 majors, namely Business and Motorcycle Engineering, Multimedia, Graphic Design, and Sharia Banking and the current number of students is quite large, namely 537. The teacher keeps track of attendance for each topic in each class. The student attendance process is carried out manually, namely recording in the attendance book. Attendance book documents are susceptible to damage such as tearing, getting wet, and being lost. So it will cause difficulties during the recording process at the end of the semester and it requires many attendance book documents. Apart from that, it requires storage space for attendance documents. Using RFID in the design of an automatic attendance system to track students' attendance in class and Internet of Things (IoT) infrastructure is the solution to this issue. The study employs a Waterfall method approach, with steps starting with requirements analysis, and moving on to system design, testing, implementation, and maintenance. The research results are the design of an automated student attendance system based on IoT and RFID. The attendance system for 28 students in 1 class takes 16 minutes, 4 minutes faster than the manual attendance system, which is 20 minutes. Teachers can see the results of the attendance data recap through the website interface which includes information on subjects, classes, majors, academic year, semester, names of students present, KBM date, entry time, and class exit time.